2017
DOI: 10.5812/traumamon.57680
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Acetaminophen Versus Intravenous Morphine Sulfate for Isolated Diaphyseal Long Bone Fractures: A Randomized Clinical Trial

Abstract: Objectives: Pain management is an important issue in traumatic patients. The aim of this randomized clinical trial was to compare the analgesic effect of intravenous acetaminophen with intravenous morphine sulfate in patients with traumatic diaphyseal long bone fracture. Methods: This double-blind randomized clinical trial was carried out in an academic trauma center in Mashhad, Iran, from February to October 2013. After primary modalities like limb elevation, ice and limb splinting, patients were allocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 8 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…Included studies’ pain scores ranged from 2.7 to 9.2 (mean 7.6). In 24 trials,9–14 16–30 36–38 the change in pain scores from T0 to T30 was reported, and all trials except one29 reported that all groups (paracetamol, NSAIDs or opioids) achieved clinically significant reductions in pain scores from T0 to T30. Key data were missing from 25 papers, and the lead authors were contacted to request the information,8–32 but no authors replied to requests for data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Included studies’ pain scores ranged from 2.7 to 9.2 (mean 7.6). In 24 trials,9–14 16–30 36–38 the change in pain scores from T0 to T30 was reported, and all trials except one29 reported that all groups (paracetamol, NSAIDs or opioids) achieved clinically significant reductions in pain scores from T0 to T30. Key data were missing from 25 papers, and the lead authors were contacted to request the information,8–32 but no authors replied to requests for data.…”
Section: Resultsmentioning
confidence: 99%
“…IVP was administered as a single dose of 1 g in 100 mL NS (100 ml normal saline) in 26 trials8–13 15–19 21–30 32 36–38 and at a dose of 15 mg/kg in one trial 20. The infusion rate for the administration of IVP was as a rapid bolus infusion in three trials,11 12 24 slow infusion over 5–20 min in 16 trials,8 10 13 16 18 19 21 22 25 26 29–32 36–38 and not mentioned for 8 trials 9 14 15 17 20 23 27 28. Doses of morphine were 0.1 mg/kg in 12 trials,9 13 19–23 25–28 37 5 mg/mL in 1 trial30 and 10 mg in 2 trials 18 31…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, there is currently a greater tendency towards the use of nonsteroidal antiinflammatory drugs (NSAIDs). (5)(6)(7)(8) On the other hand, NSAIDs have complications as gastrointestinal bleeding and renal failure. (9) According to aforementioned complications, it is necessary to use less complicated and more effective medications for RC.…”
Section: Introductionmentioning
confidence: 99%